Development of a fluorescence assay for highly sensitive detection of Pseudomonas aeruginosa based on an aptamer-carbon dots/graphene oxide system. Issue 57 (19th September 2018) - Wang, Hongying; Chi, Zhe; Cong, Ying; Wang, Zhuangzhuang; Jiang, Fei; Geng, Jiayue; Zhang, Peng; Ju, Peng; Dong, Quanjiang; Liu, Chenguang
Abstract : The fluorescence assay for detecting Pseudomonas aeruginosa was achieved by the aptamer-CDs/GD system which exhibited obvious fluorescence recovery when encountered the cells of P . aeruginosa . Abstract : An aptamer-based fluorescence assay for culture-independent detection of Pseudomonas aeruginosa was developed. This assay was enabled by highly specific aptamers conjugated with photoluminescent carbon dots (CDs) as the fluorescent probe and graphene oxide (GO) as the quencher. Specially, high-throughput sequencing was achieved during systematic evolution of ligands via exponential enrichment (SELEX) for accurate recognition of aptamers. This assay displayed high specificity towards P. aeruginosa and was resistant to interference by other ubiquitous bacteria including Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Enterococcus faecalis, and Clostridium perfringens . After the conditions were optimized, this assay achieved a wide detection range for P. aeruginosa varying from 10 1 CFU mL −1 to 10 7 CFU mL −1 . Notably, it approached an excellent detection limit as low as 9 CFU mL −1 . Therefore, this fluorescence assay was considered successfully developed for highly sensitive detection of P. aeruginosa . This assay also detected the contamination of P. aeruginosa in tap water and commercial bottled water, thereby suggesting its potential application in real water samples.